PERKEMBANGAN AFEKTIF SISWA SDN 03 MANGLIAWAN MALANG DI ERA DISRUPSI MASA PANDEMI - Muchamad Khilmi; Devi Wahyu Ertanti; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
The theme that the researchers took was about the researchers' interest in students' affectiveness. After that the researcher conducted a study entitled "Affective Development of Students at SDN 03 Mangliawan Malang in the Disruption Era of the Pandemic Period". As for the purpose of my research is: (1) Describe the affective development of elementary school students in the era of disruption during the pandemic. (2) Describe the role of parents in the affective development of elementary school students in the era of disruption during the pandemic. From these objectives, the researchers used the type of qualitative research.